Investigation of circulatory and tissue-specific metabolomic biomarkers in valvular heart disease using mass spectrometry - Mutithu, Daniel Wakiri (Department of Medicine, 2026)
The work presented in this thesis was based on an investigation of the circulatory and tissue specific metabolic biomarkers in patients with rheumatic heart disease (RHD) and degenerative aortic stenosis (AS), compared to matched, healthy controls. The study hypothesis was that cardiac tissue obtained from heart valve biopsies from RHD and degenerative AS patients would have distinct histological features. The second hypothesis was that severe RHD and degenerative AS patients have distinct serum and tissue specific metabolic profiles. The third hypothesis was that pathologic regions on heart valves would have distinct spatial metabolomic profiles compared to non-diseased regions of the valves. Whole blood samples were collected from matched participants with a diagnosis of RHD and degenerative AS, as well as matched controls recruited from the Cardiac Clinic at Groote Schuur Hospital. Valve tissue samples were collected from patients undergoing valve replacement surgery at Groote Schuur Hospital. Haematoxylin and eosin staining was used to assess the histopathological features of the heart valves. Untargeted metabolomics was performed on serum and valve tissues using ultra-performance liquid chromatography with quadrupole time-of-flight mass spectrometry. In-situ biomarker localisation was performed with matrix assisted laser desorption ionisation mass spectrometry imaging. Univariate and multivariate statistical analyses was used to explore covariation with the potential metabolomic biomarkers and bioinformatics tools used to explore the gene-metabolite interactions. The study had several key observations. First, though rare, we reported that chronic RHD may be admixed with features of acute rheumatic fever, within the same patient. Second, using an untargeted/discovery approach, we identified metabolites involved in the major energetic pathways, amino acids metabolism, and inflammation regulation which were altered in RHD and degenerative AS. The identified biomarkers were associated with cardiovascular imaging-based remodelling parameters. Third, RHD patients with single or double valve replacement, and degenerative AS patients demonstrated distinct tissue-specific metabolic signatures. Metabolites involved in amino acid, fatty acid, and crucial biomolecule metabolism were associated with histopathological and cardiovascular imaging-based parameters of valvular heart disease. Finally, tissue-specific metabolites could be localised on valve biopsies obtained from RHD and degenerative AS participants, though no differences were observed between the two group.